The ’Rubiales case’ and the #SeAcabó movement in the press in Spain and the UK: between politics and gender - López-Carrión, Alberto E.; Sanahuja-Peris, Guillermo (Historia y Comunicación Social, 2024)
This research aims to describe the characteristics of the media coverage of the ‘Rubiales case’ in Spain and the United Kingdom. To this end, a methodological design is proposed for a sample of news items related to the case published in 24 digital newspapers over 25 days, combining quantitative and descriptive content analysis of the contents that make mention of this issue, to then carry out a qualitative and interpretative analysis of a representative sample of news items. The results reveal differences in news treatment not only in terms of volume of information, but also in terms of perspective. The coverage of the ‘Rubiales case’ has been strongly politicised, constituting a platform on which to expose different gender discourses.